2000
DOI: 10.1007/s000490050010
|View full text |Cite
|
Sign up to set email alerts
|

Bark volatiles from nonhost angiosperm trees of spruce bark beetle, Ips typographus (L.) (Coleoptera: Scolytidae): Chemical and electrophysiological analysis

Abstract: Volatiles from bark of three nonhost angiosperm trees of Ips typographus (Coleoptera: Scolytidae) (Betula pendula, B. pubescens, and Populus tremula) were collected by headspace sampling and direct solvent extraction in June 1998, and identified and quantified by coupled gas chromatographic-mass spectrometry (GC-MS). Only small amounts of bark volatiles were detected in the aerations in situ from undamaged stems of the nonhost trees. In headspace volatiles from bark chips the two birch species had a similar od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 42 publications
3
85
0
Order By: Relevance
“…The outlet for the EAD was held in a humidified air-stream flowing at 0.5 m/s over an I. typographus antennal preparation (Zhang et al 2000). A glass capillary indifferent electrode filled with 0.9 % NaCl saline (Ilsanta, Vilnius, Lithuania) and grounded via a silver wire was inserted into the severed beetle head with antennae.…”
Section: Gas Chromatography-electroantennogram Detectionmentioning
confidence: 99%
“…The outlet for the EAD was held in a humidified air-stream flowing at 0.5 m/s over an I. typographus antennal preparation (Zhang et al 2000). A glass capillary indifferent electrode filled with 0.9 % NaCl saline (Ilsanta, Vilnius, Lithuania) and grounded via a silver wire was inserted into the severed beetle head with antennae.…”
Section: Gas Chromatography-electroantennogram Detectionmentioning
confidence: 99%
“…Antennal responses to nonhost leaf and bark volatiles have been found by using the coupled gas chromatography-electroantennographic detection (GC-EAD) or GC-SCR (single cell recording) techniques in over 10 species of bark beetles (Tømmera˚s & Mustaparta, 1989;Tømmera˚s & Mustaparta, 1989;Huber et al, 2000a;Zhang et al, 2000), two cerambycid beetles (Barata et al, 2000;Suckling et al, 2001) and a bark tortrix moth (McNair et al, 2000). For example, in GC-EAD analyses of Betula pendula Roth, B. pubescens Ehrh and Populus tremula L. leaf and bark volatiles, the antennae of I. typographus strongly responded to C 6 -alcohols (GLVs): 1-hexanol and (Z)-3-hexen-1-ol from both leaves and bark, and (E)-2-hexen-1-ol from the nonhost intact leaves (Zhang et al, 1999a and to trans-conophthorin (tC) and C 8 -alcohols: 3-octanol and 1-octen-3-ol from the nonhost bark .…”
Section: Introductionmentioning
confidence: 99%
“…Other reports showed similar disruption by alcohols, with the two most effective being (Z)-3-hexen-1-ol and (E)-2-hexen-1-ol [25]. 1-Octen-3-ol was not only identified in the bark volatiles of European birch and aspen [30,31] but also identified in females of D. ponderosae, D. rufipennis, and D. pseudotsugae [14]. Further field tests found that 1-octen-3-ol was repellent to all three Dendroctonus spp.…”
Section: Discussionmentioning
confidence: 52%